Terminal Complement Pathway Deficiency in an Adult Patient with Meningococcal Sepsis - F. Staels; W. Meersseman; P. Stordeur; K. Willekens; S. Van Loo; A. Corveleyn; I. Meyts; G. Meyfroidt; R. Schrijvers (Case Reports in Immunology)
The complement system is an essential part of our innate immune system. Three enzymatic activation pathways are described, all converging into a common terminal pathway which causes lysis of the target cell. Late complement deficiencies (LCDs) are typically diagnosed in children or adolescents with invasive meningococcal disease (IMD). However, IMD can also be a first manifestation in adulthood and should prompt for the evaluation of the LCD. We report the case of a young adult with IMD who was found to have a LCD, caused by a compound heterozygous mutation in C6. His vaccination status was optimized and prophylactic antibiotic treatment was initiated. By means of this case, we would like to raise awareness of underlying LCD in (young) adults presenting with IMD by N. meningitidis. Screening for complement deficiencies after IMD, followed by genetic testing, can be lifesaving and allows for genetic counselling. In addition, we discuss the diagnosis and treatment of LCD.